Application of fluorescein sodium in breast cancer brain-metastasis surgery - Xiao S; Zhang J; Zhu Z; Li Y; Zhong W; Chen J; Pan Z; Xia H (Cancer Management and Research, 2018)
Shi-yin Xiao,1 Ji Zhang,2,* Zheng-quan Zhu,3,* You-ping Li,4,* Wei-ying Zhong,5 Jian-bin Chen,6 Zhen-yu Pan,7 Hai-chen Xia3 1Department of Neurosurgery, Second Affiliated Hospital of Guangzhou Medical University, Guangzhou 510260, China; 2Department of Neurosurgery, State Key Laboratory of Oncology in South China, Sun Yat-sen University Cancer Center, Collaborative Innovation Center for Cancer Medicine, Guangzhou 510060, China; 3Department of Neurosurgery, Tumor Hospital Affiliated of Xinjiang Medical University, Xinshi District, Urumqi, Xinjiang 830011, China; 4Department of Neurosurgery, First Affiliated Hospital of Nanchang University, Nanchang, Jiangxi 330046, China; 5Department of Neurosurgery, Qilu Hospital, Shandong University, Jinan 250012, China; 6Department of Neurosurgery, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan 430030, China; 7Department of Radiation-Oncology, First Hospital of Jilin University, Changchun 130021, China *These authors contributed equally to this work Objective: Surgical resection serves an important role in the multidisciplinary treatment of cerebral metastases (CMs). Conventional white-light, microsurgical, and circumferential stripping of CMs is standard neurosurgical procedure, but is associated with a high recurrence rate. Based on this outcome, there is an urgent need for a new surgical strategy, such as fluorescence-guided resection, for CMs, in order to achieve total removal. Methods: A retrospective study was carried out in 38 patients clinically and pathologically diagnosed with breast cancer brain metastasis at three medical centers from May 2012 to June 2016. The study comprised group 1 (fluorescein-guided surgery) and group 2 (standard microsurgery). In group 1, 5 mg/kg of fluorescein sodium was injected intravenously after an allergy test and before general anesthesia for 17 patients. A yellow 560 filter was employed for microsurgical tumor resection. Group 2 consisted of 21 patients for whom fluorescein was not administered. Results: Surgical outcomes were assessed concerning the extent of resection and Karnofsky performance status. Gross total resection was achieved in these patients, with high fluorescence markedly enhancing tumor visibility. The extent of resection had a powerful influence on performance status. Overall survival after CM was 24.1 months in patients given fluorescein and was 22.8 months in the nonfluorescein group. Conclusion: Fluorescein-guided surgery is a simple, safe, and practical method to resect breast cancer brain metastasis, and leads to a higher proportion of resection compared to common microsurgery. This offers a tremendous advantage when navigating a tiny tumor, and improves the quality of life of patients with CM. Keywords: fluorescein sodium, breast cancer brain metastasis, fluorescence-guided surgery, extent of resection, KPS